Synthetic and Antimicrobial Studies of Some new Chalcones of 3-Bromo-4-(p-tolyl sulphonamido) acetophenone - Miss Rashmi Jain; O. P. Chourasia; J. Tirumala Rao (E-Journal of Chemistry)
Eleven new chalcones have been sysnthesised by condensing 3-bromo-4-(p-tolyl sulphonamido) acetophenone with different aromatic aldehydes using the method or Rohrman et al. The antimicrobial activity of these chalcones has been tested by adopting “paper disc diffusion plate method”, against various pathogenic fungi and bacteria. It has been found that the chalcones have considerable antifungal activity but less antibacterial activity. The results show that these chalcones may find use as antifungal agents.